(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This comprehensive article provides a concise yet informative overview of the history of Uzbekistan, spanning from ancient civilizations to the modern era. It highlights key historical events, including the rise of Islam, the Timurid Empire, colonialism, Soviet rule, and independence. The article delves into Uzbekistan’s rich cultural heritage, architectural marvels, and the challenges and opportunities facing the country today. Additionally, it discusses Uzbekistan’s regional dynamics, cultural revival efforts, and international engagement. With a well-rounded approach, the article offers valuable insights into Uzbekistan’s past, present, and future, making it a valuable resource for readers interested in Central Asian history and culture.